Perancangan Desain Kemasan Inovatif untuk Meningkatkan Daya Tarik Produk UMKSM Mie Lidi Krezz - Rahmad Akbar (Jurnal Sains dan Ilmu Terapan, 2024)
The rapid development of the global market is in the global industry where companies must have the ability to compete globally in facing the progress of the times. Therefore, the development of this global market is a challenge for companies, including UMKM Mie Lidi Krezz in Bangkinang City, which must be able to compete to present to consumers the best taste, quality, service, price, and packaging design compared to other competing products, so that they can continue to maintain their performance. Therefore, it is necessary to develop the packaging design of the Mie Lidi Krezz product in Bangkinang City by applying the Kansei Engineering approach. This approach takes into account the emotional and psychological aspects of product packaging with the aim of creating a positive experience for consumers.